Peningkatan Sistem Keamanan One Time Password (OTP) Pada Token Aplikasi Computer Based Test (CBT) Menggunakan Algoritma SHA-256 - Iswatun Khasanah , Nur; Heru Mujianto , Ahmad; Widoyoningrum, Sri (Inovate, 2023)
System security is often used in schools to secure school data or other data. As in Hasbullah Bahrul Ulum Creative Vocational High School (SMK). The school still uses the manual method, which still has many problems, including the lack of question paper or answer sheets and the school's quite a lot of costs. To overcome this problem the researchers created a Computer Based Test (CBT) application with OTP security if when logging in the username and password are known to other people. In the research conducted using the Secure Hash Algorithm 256 bit (SHA-256) which is used to generate OTP. The process for finding the appropriate string value is calculated flexibly which results in producing a message digest and can search for different string values and produce a message digest that has the same value, so SHA-256 can be said to be an accurate security. The result of this research is a CBT application with token code security, from the SHA-256 method it generates a token code used for student login. The token functions as security when accessing the login system if someone else knows the username and password, that person cannot log in if they don't have the token code and the token code is only given once during the exam unless there are problems. Keywords: Security, Computer Based Test, One Time Password, Secure Hash Algorithm,Token